Roles of CONSTITUTIVE PHOTOMORPHOGENIC 10 in Arabidopsis stomata development - Delgado, Dolores (Landes Bioscience, 2012)
Stomata are epidermal bi-celled structures that differentiate within special cell lineages initiated by a subset of protodermal cells. Recently, we showed that the Arabidopsis photomorphogenic repressor COP10 controls specific cell-lineage and cell-signaling developmental mechanisms in stomatal lineages. Loss-of-function cop10-1 mutant cotyledons and leaves produced (in the light and in the dark) abundant stomatal clusters, but nonlineage epidermal cells were not affected. Here we examine COP10 role in hypocotyls, cylindrical organs displaying a distinct epidermal organization with alternate files of protruding and non-protruding cells, with the latter producing a limited number of stomata. COP10 prevents stomatal clusters and restricts stomata production in hypocotyls; these roles are specific to lineage cells as in cotyledons, since COP10 loss of function does not elicit stomatal fate in nonlineage cells; COP10 also sustains the directional cell expansion of all hypocotyl epidermal cell types, and seems necessary for the differentiation between protruding and non-protruding cell files.